2009
DOI: 10.1139/f09-144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance of alternative management models of Pacific salmon (Oncorhynchus spp.) in the presence of climatic change and outcome uncertainty using Monte Carlo simulations

Abstract: An important management challenge is to maintain productive populations of Pacific salmon ( Oncorhynchus spp.), despite highly variable environments and our weak understanding of future climatic conditions and mechanisms that link them to salmon. This understanding could be improved by including environmental covariates in salmon population models and applying advanced “meta-analyses” to large data sets to better estimate underlying functional relationships. However, the performance of such models needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…These results are qualitatively similar to those obtained in the present study. Dorner et al (2009) evaluated management models for Pacific salmon. They used several assessment and prediction models and found that although complex models performed better in some cases, their benefits were small.…”
Section: Comparison Of Obtained Results With Those Reported In Literamentioning
confidence: 99%
“…These results are qualitatively similar to those obtained in the present study. Dorner et al (2009) evaluated management models for Pacific salmon. They used several assessment and prediction models and found that although complex models performed better in some cases, their benefits were small.…”
Section: Comparison Of Obtained Results With Those Reported In Literamentioning
confidence: 99%
“…Balance harvest across multiple subpopulations in Bristol Bay (Hilborn et al, 2003) Use stock assessments with temporally variable productivity Increased complexity of assessment models (Dorner et al, 2009) Declining productivity in northern Alaska salmon (Collie et al, 2012) Multidecadal oscillations and directional anthropogenic climate change…”
Section: May Require Coordination Across Multiple Management Organizamentioning
confidence: 99%
“…Model-free forecasting methods that account for nonlinear population dynamics and physical forcing from climate may also hold promise for shortterm forecasts for one or a couple years ahead (Deyle et al, 2013). The additional sources of bias and uncertainty in more complex statistical methods appear to limit their practical utility at the moment (Dorner et al, 2009;Glaser et al, 2013). Part of the challenge is to separate the effects of climate from those of fishing because both are often operating at the same time (Haltuch and Punt, 2011).…”
Section: Accounting For Climate Effects In Stock Assessmentsmentioning
confidence: 99%
“…As well, a Management Strategy Evaluation (MSE) is needed to evaluate management options using a set of alternative but plausible system models (not just "the best" single model or the one "new and improved" model) to represent uncertainties in our understanding of the system's underlying dynamic processes. Other types of uncertainty, such as 8 those that cause deviations between management targets and actual outcomes, could mask or swamp any improvement garnered from a better system model, as was found, for example, in a MSE that included alternative models for sockeye salmon (Oncorhynchus nerka) populations (Dorner, Peterman & Su, 2009). …”
Section: Model Complexitymentioning
confidence: 99%